The Use Of Technology In English Language Learning In The Digital Era - Aldo Suriadi; Wirda Lestari Pasaribu; Yani Lubis (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid advancement of digital technology has significantly transformed English language learning, particularly in grammar instruction. This literature review examines the opportunities and challenges of integrating technology into English grammar education. By analyzing various studies, the review highlights effective strategies such as the use of e-learning platforms, mobile-assisted language learning, gamification, and collaborative online tools that enhance learner engagement, motivation, and proficiency. The review also identifies critical factors influencing successful implementation, including teacher readiness, digital literacy, and equitable access to technology. Challenges such as the digital divide, data privacy concerns, and the need for culturally sensitive instructional materials are discussed. The study concludes that while technology offers promising avenues for improving grammar learning, comprehensive teacher training and infrastructure development are essential to maximize its benefits. Recommendations for future research and policy development emphasize adaptive learning systems and inclusive pedagogical strategies to foster effective and equitable English grammar education in the digital era.